A base excited mixed-connected inerter-based quasi-zero stiffness vibration isolator with mistuned load. Issue 25 (12th October 2022) - Wang, Yong; Li, Hao-Xuan; Jiang, Wen-An; Ding, Hu; Chen, Li-Qun
Abstract: The dynamic characteristic of the mixed-connected inerter-based quasi-zero stiffness (MC-IQZS) vibration isolator with mistuned load under base excitation is investigated. The Harmonic Balance Method (HBM) is utilized to acquire the dynamic response, the varying tendencies of backbone curve and dynamic response are studied, the stability analysis and unstable regions are conducted to show the occurred complicated dynamic response, the isolation performance is studied. As a mistuned load is imposed, the base excited MC-IQZS vibration isolator could acquire smaller resonance peak, smaller absolute displacement and acceleration transmissibilities in high-frequency band than the QZS one, only the isolation frequency band is narrower.